Feature Column

Finite-dimensional Feynman Diagrams

Feature Column Archive

2. Facts from calculus and their d-dimensional analogues

The basic fact from calculus that powers the whole discussion is:

Proposition 1  

$\displaystyle \int_{-\infty}^{\infty} dx~~ e^{ -\frac{\scriptstyle a}{2}x^2} = \sqrt{\frac{2\pi}{a}}.$

The identity with  a = 1 is proved by the trick of calculating the square of theintegral in polar coordinates. The general identity follows by change of variablefrom  x to $ x{\sqrt a}$ .

This fact generalizes to higher-dimensional integrals. Set   v = (v1, ..., vd)and  dv = (dv1 ... dvd),and let  A  be a symmetric  dby d   matrix.

Proposition 2  

$\displaystyle \int_{{\bf R}^d} d{\bf v} ~~\exp(-{\scriptstyle\frac{1}{2}}{\bf v}^tA~{\bf v}) = (2\pi)^{d/2} (\det A)^{-1/2}.$

We use the fact that a symmetric matrix A isdiagonalizable: there exists an orthogonal matrix U(so Ut = U-1)such that UAU-1 is the diagonal matrix Bwhose onlynonzero entries are b11, ... , bddalong the diagonal. Then A = U-1BUand vtAv = vt U-1B U v =vtUtB U v =wtB w where w = Uv,using Ut = U-1 and (Uv)t =vtUt. Since Uis orthogonal   detU = 1   and the change of variable from v to wdoes notchange the integral:

$\displaystyle \int_{{\bf R}^d} d{\bf v} ~~\exp(-{\scriptstyle\frac{1}{2}}{\bf v......\int_{{\bf R}^d} d{\bf w} ~~\exp(-{\scriptstyle\frac{1}{2}}{\bf w}^tB~{\bf w})=$

$\displaystyle \int_{{\bf R}^d} d{\bf w} ~~\exp(b_{11}(w^1)^2 +\cdots + b_{dd}(w^d)^2) =$

$\displaystyle (\int_{-\infty}^{\infty} dw^1~\exp(b_{11}(w^1)^2))~\cdots~(\int_{-\infty}^{\infty} dw^d~\exp(b_{dd}(w^d)^2))=$

$\displaystyle (\sqrt{2\pi}/\sqrt{b_{11}})~\cdots~ (\sqrt{2\pi}/\sqrt{b_{dd}})=$

$\displaystyle (2\pi)^{d/2} (\det B)^{-1/2} = (2\pi)^{d/2} (\det A)^{-1/2}.$

Proposition 3  

$\displaystyle \int_{-\infty}^{\infty} dx \, e^{-\frac{a}{2}x^2 + bx} =\sqrt{\frac{2\pi}{a} } e^{b^2/2a}\, .$

This follows from Proposition 1 by completion of the square in the exponent and a change of variables.

The generalization to ddimensions replaces awith Aas before and bwiththe vector b = (b1, ... , bd)

Proposition 4  

$\displaystyle \int_{{\bf R}^d} d{\bf v} ~~\exp(-{\scriptstyle\frac{ 1}{ 2}}{\bf......)^{d/2} (\det A)^{-1/2} \exp({\scriptstyle\frac{1}{2}}{\bf b}^tA^{-1}{\bf b}). $

This is proven exactly like Proposition 2.If we write this integral as Zbthen the integral of Proposition 2 is Z0and this proposition can be rewritten as

$\displaystyle Z_{\bf b} = Z_0 \exp({\scriptstyle\frac{1}{2}}{\bf b}^tA^{-1}{\bf b}) . $

Welcome to the
Feature Column!

These web essays are designed for those who have already discovered the joys of mathematics as well as for those who may be uncomfortable with mathematics.
Read more . . .

Search Feature Column

Feature Column at a glance

Show Archive

Browse subjects